Природа і кінетика нестаціонарного поглинання світла плівками С60, наведеного фемтосекундними лазерними імпульсами - Gorishnyi, M.P.; Pavlov, I.A.; Kovalchuk, A.V. (Publishing house "Academperiodika", 2021)
Using the "pump–probe" technique, the structure and the temporal evolution of the light absorption in С60 films induced by femtosecond laser pulses inthe spectral range of 2.04–2.37 eV and the pulse time interval of 0–882 ps have been studied. С60 films 200 nm in thickness were obtained by thermal evaporation onto quartz substrates in a vacuum of 0.65 mPa and at room temperature. In the probe range of 2.04–2.37 eV, the shape of the absorption spectrum induced by femtosecond laser pulses in a С60 film consists of bands at 2.097, 2.164, 2.209, 2.262, 2.299, and 2.331 eV. The bands at 2.097, 2.209, and 2.262 eV are induced by electron transitions between the energy bands created by zero vibronic levels of the S0 state and nonzero vibronic levels of S1 state of С60 molecules. For the first time, it has been shown that the "hot" bands at 2.164, 2.299, and 2.331 eV result from the electron transitions either between the energy bandscreated by three nonzero vibronic levels of S0 state, on the one hand, and the zero vibronic level of S2 state, on the other hand, or between the energy bands created by three nonzero vibronic levels of S1 state, on the one hand, and the zero vibronic level of S4 state, on the other hand, of С60 molecules. The decreasing temporal kinetics of the optical density D under the induced absorption in С60 films was approximated by a sum of three exponential terms in the pulse time interval of 0–882 ps. For probe photons with the energy E = 2.217 eV, the following values of relaxation times were obtained: τr1=(1.04±0.13)ps, τr2=(5.81 ± 0.94) ps, and τr3=(108.0 ± 9.3) ps . The approximation of those kinetics by the Kohlrausch function (the "stretched" exponent) allowed us to evaluate the effective relaxation time τr as 6.0 ps, which is close to the τr2-value. The electron subsystem of С60 films needs the time interval Δt>882 ps to relax into the equilibrium state. The quantities τr1 and τr2 $ are found to depend significantly on the approximation time interval and the method used for averaging the kinetics ΔDn(t). For τr3, this dependence is much weaker.